Carbon and nutrient dynamics under long-term nutrient management in tropical rice-wheat-jute system. Issue 11 (19th September 2018) - Mazumdar, S.P.; Kundu, D.K.; Saha, A.R.; Majumdar, B.; Saha, R.; Singh, A.K.; Barman, D.; Ghosh, D.; Dey, R.; Behera, M.S.; Mitra, S.; Bhattacharyya, P.
ABSTRACT: Impacts of 43-year nutrient management on carbon (C) and nutrient dynamics were studied in a rice-wheat-jute system in tropical India. Carbon dynamics was investigated on the basis of its distribution of labile (microbial biomass C, permanganate oxidizable C and water soluble C) and slow pools (Walkley Black oxidizable organic C), its indices (C pool index, lability index) and C management index (CMI) at different soil depths. Nutrient dynamics was judged by major nutrients availability, and related soil enzymatic activities. We studied seven treatments including unfertilized control, 100% NPK (N:P2 O5 :K2 O 60:30:60), 50% NPK, 150% NPK, 100% NP, 100% N, 100% NPK + farm yard manure (10 tonnes FYM ha −1 ). Nutrients availability and soil enzymatic activities were significantly increased under balanced fertilization (100% NPK + FYM) over other treatments. Labile, slow and total C was also found highest in 100% NPK + FYM. Enhanced C indices under 100% NPK + FYM over 100% NPK and other treatments signified the importance of long term balanced fertilization on soil C stabilization. Lability indexes were lower at sub-soil (30-45cm). In terms of favourable nutrient dynamics and CMI, balanced application of NPK plus organics were recommend for long term sustainability of rice-wheat-jute system in tropics.